2020
DOI: 10.18502/jad.v13i4.2238
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Susceptibility of Culiseta longiareolata (Diptera: Culicidae) to Different Imagicides, in Eastern Azerbaijan, Iran

Abstract: Background: Culiseta longiareolata is an important vector for many human diseases such as brucellosis, avian influen-za and West Nile encephalitis. It is likely an intermediate host of avian Plasmodium that can transmit Malta fever. The aim of this study was to determine the susceptibility level of Cs. longiareolata to different classes of imagicides which are recommended by World Health Organization . Methods: Larval stages of the Cs. longiareolata were collected from their natural habitats in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…In our study, all three genera of collected mosquitoes were found in natural larval habitats having some vegetation. Among three genera, Culex species approximately were collected from different types of larval habitats and this finding was similar to study conducted in Northwestern Iran ( 21 ). Cx.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, all three genera of collected mosquitoes were found in natural larval habitats having some vegetation. Among three genera, Culex species approximately were collected from different types of larval habitats and this finding was similar to study conducted in Northwestern Iran ( 21 ). Cx.…”
Section: Discussionsupporting
confidence: 86%
“…subochrea mosquitoes were collected. In contrast, in East Azerbaijan ( 21 ), Kurdistan and Kermanshah ( 17 ) provinces. Cs.…”
Section: Discussionmentioning
confidence: 99%
“…Elle est considérée comme vecteur important de plusieurs maladies, telles que la Brucellose, la grippe aviaire, et l'Encéphalite du Nil Occidental (Brunhes et al, 1999). C'est un hôte intermédiaire de Plasmodium aviaire qui peut transmettre la fièvre de Malte (Hazratian et al, 2019). Elle peut aussi provoquer de la Tularémie et des maladies arboviroses (Soltanbeiglu et al, 2020).…”
Section: Resultats Et Discussionunclassified
“…There are several reports of insecticide resistance in malaria and West Nile vectors in Iran [13,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Studies on non-pathogenic fungi of mosquitoes are very scarce and have not been done in Iran.…”
Section: Effects Of Fungi On Morphological or Behavioural Manifestations Of Mosquito Larvaementioning
confidence: 99%